Proposed observation park at Rabung Likas, Kota Kinabalu, Sabah - Mansyur, Alfian; Said, Ismail (2007)
This design proposal prepares a master plan for a community for the urban communities in Kota Kinabalu. Thee 12-hectare park is located at Rabung Likas dominated by three hills overlooking the Likas Bay and residential communities of the city. The physical resources the hills and secondary forest dominated by acacia tress areas and scenic views. From the three hills, only is left undisturbed by the development of the city. The design concept for this project is sense of naturalness; a place that affords people to get contact with nature. This concept is supported with two concerns: ecological planning and balance of urban development in the city. Naturalness of material dominates the design of the park. The design proposal divides the site into four major zones which are (i) entrance area that consist of parking and tram station, (ii) observation plaza that consist of commercial and administration building, (iii) nature area that consist of recreational activity such as jogging trail, jungle trail, observation deck and nature viewing plaza, and (iv) an observation area with watch towers and observation bridge. The proposal emphasizes on active recreational activities such as jogging, playing, and exercising as well as passive ones such as outdoor learning, viewing and observing. Hence the design provides several features including observation towers, jogging trail, jungle trail, observation decks, nature viewing plaza and tram. This community park may become a resource asset to the urban dwellers of the city for recreation and tourism. The site becomes part of the green lung of the city which may support the concept of â€œcity in tropical forest.â€